PANDANGAN PENUMPANG TERHADAP PELAYANAN TRANS METRO PEKANBARU - Hantoro, Yoseph Dwi; ", Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This thesis is submitted to meet the requirements for a bachelor's degree in sociology with the title "Passenger's View of Trans Metro Pekanbaru". The problems in this thesis are (1) How do passengers view Trans Metro Pekanbaru services? (2) What are the factors that influence the passenger's view of the Trans Metro Pekanbaru?. The purpose of this research is to find out how the services that have been provided by Trans Metro Pekanbaru to the public and to find out how the passengers view the services that have been given by Trans Metro Pekanbaru. This research uses descriptive quantitative research method, this research was conducted in the Trans Metro Pekanbaru bus and the Trans Metro Pekanbaru bus stop which hopefully will obtain the data needed by researchers. From the results of this study, it can be seen how the passenger's view of Trans Metro Pekanbaru is where the passenger's view of the bus stop is still not good, the passenger seat and priority seat facilities are good, but the arrival time and travel time are not good, while for flight attendants, passengers give good judgment. Keyword: Views, Services, Trans Metro Pekanbaru.